2018
DOI: 10.3892/or.2018.6196
|View full text |Cite
|
Sign up to set email alerts
|

TTF1‑NP induces protective autophagy during apoptosis by inhibiting the Akt/mTOR pathway and activating JNK in human liver cancer cells

Abstract: TTF1‑NP is a flavonoid nanoparticle based on 5,2',4'‑trihydroxy‑6,7,5'‑trimethoxyflavone (TTF1), which is derived from the medicinal plant Sorbaria sorbifolia that grows in the Changbai Mountain. We previously demonstrated antitumor effects of TTF1‑NP in human hepatoma including induction of apoptosis and inhibition of angiogenesis, migration and invasion. Herein, we examined the effects of TTF1‑NP on autophagy and its relationship with apoptosis, and explored potential underlying mechanisms in human hepatoma … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…Therefore, we detected a stemness-destructed autophagy induced by mTOR inhibitors, which is supported by previous studies 23 , 24 . Although other studies suggests that autophagy is protective 39 , 40 , we argue that tumor cells have to derive adequate nutrient substance to guarantee basic survival-related sustainment upon various stresses by sacrificing some aggressive behaviors, such as stemness maintenance. Similarly, we detected that mTOR inhibitors, an autophagy inducer, exerted an effect of suppression on the self-renewal and tumorigenicity of GICs and could be blocked by using autophagy inhibitors in vitro.…”
Section: Discussionmentioning
confidence: 67%
“…Therefore, we detected a stemness-destructed autophagy induced by mTOR inhibitors, which is supported by previous studies 23 , 24 . Although other studies suggests that autophagy is protective 39 , 40 , we argue that tumor cells have to derive adequate nutrient substance to guarantee basic survival-related sustainment upon various stresses by sacrificing some aggressive behaviors, such as stemness maintenance. Similarly, we detected that mTOR inhibitors, an autophagy inducer, exerted an effect of suppression on the self-renewal and tumorigenicity of GICs and could be blocked by using autophagy inhibitors in vitro.…”
Section: Discussionmentioning
confidence: 67%
“…Previous studies have reported that activating the Akt/mTOR signaling pathway promotes inflammation and apoptosis; on the contrary, inhibiting the Akt/mTOR signaling pathway can alleviate the occurrence of inflammation in hµMan liver cancer cells [21]. Data show that platycodin D treatment diminished phosphorylation of PI3K/Akt/mTOR signaling pathway in A549 and the NCI-H460 cells [22].…”
Section: Discussionmentioning
confidence: 85%
“…Consistently, we found that autophagy was inhibited in ASPP2 haploinsufficient (ASPP2 +/− ) mice after 70% PH X , indicating that ASPP2 may promote autophagy. Considering that mTORC1 is one of the upstream regulators of autophagy 2729 and that ASPP2 regulates mTORC1, we speculated that ASPP2 may regulate autophagy through the mTORC1 pathway, which may be a novel finding that warrants further exploration.…”
Section: Discussionmentioning
confidence: 99%